IFN-γ regulates the transformation of microglia into dendritic-like cells via the ERK/c-myc signaling pathway during cerebral ischemia/reperfusion in mice. (December 2020) - Zhang, Haiyu; Zhang, Tongshuai; Wang, Dandan; Jiang, Yixiang; Guo, Tieyun; Zhang, Yao; Zhu, Fan; Han, Kaiyu; Mu, Lili; Wang, Guangyou
Abstract: Cerebral ischemia-reperfusion injury induces a secondary immune inflammatory reaction that exacerbates brain injury and clinical prognosis. Dendritic cells (DCs) and microglia are both important regulators of neuroinflammation. Studies have confirmed that a large number of cells express the DC surface marker CD11c in the ischemic area, and some of these cells also express microglial markers. However, the specific mechanism of transformation between microglia and DCs and their roles in the process of cerebral ischemia-reperfusion injury are still not clear. In this study, we established a mouse model and flow cytometry was used to detect the expression of mature DC surface molecules in activated microglia. IFN-γ knockout mice were used to determine the regulatory effect of IFN-γ on microglial transformation. We found that CD11c + cells were derived from microglia after ischemia-reperfusion injury, and this group of cells highly expressed MHC-II molecules and other costimulatory molecules, such as CD80 and CD86, which were regulated by IFN-γ and its downstream signaling molecules ERK/c-myc. In summary, our results showed in cerebral ischemia-reperfusion injury, IFN-γ regulates the transformation of microglia to DC-like cells. Microglial-derived DC-like cells possess the ability to present antigens and activate naïve T cells which is regulated by the ERK/c-myc signaling pathway. Highlights: The present study firstly verified the regulation function of IFN-γ on microglia after cerebral ischemia/reperfusion, and this regulation is via ERK/c-myc signaling pathway. Microgliacould acquire antigen presentation functions during this process and thus involved in the neuro inflammation reactions.